Constructing Engagement Method of Attracting Viewers Attention to Digital Advertisement - Kurniawan, Agung Budi; Wulandari, Sri (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2023)
This research analyzed engagement methods of five Instagram digital advertisements by using an instrument including content, types of advertisement, human and non-human figures, color involvement, size, and written text by using content analysis. Combining the main product with supporting materials, presenting product ingredients, and price information is the main finding of the content. Findings of four main advertisement types includes informing, entertaining, persuading, and encouraging viewers to be critical thinkers. The involvement of human and non-human beings is recommended to be applied only for coherence specific products. The application of the figures should consider the social, cultural, and belief values of potential viewers. Color findings show usage of lightening and complex colorful advertisements obtain viewers’ serious attention. The size and location of the pictures were found to represent the priority order of introducing products to customers. Meanwhile, short written texts were found to be the best performance to present interactive and communicative written text in a digital advertisement. In the discussion, this research proposes the prototype of the engagement method to attract viewers’ attention to a digital advertisement that consists of a social survey or observation, psychical performance, written text, and implicit meaning construction.Keywords: Engagement, attracting, attention, digital, advertisement ABSTRAKPenelitian ini menganalisa metode pendekatan dalam lima iklan digital di Instagram dengan menggunakan instrument yang meliputi konten, jenis iklan, figure manusia dan bukan manusia, warna, ukuran, dan teks tertulis dengan content analysis. Temuan pada konten meliputi penggunaan materi utama dan pendukung, dan harga produk iklan. Empat jenis iklan ditemukan dengan tujuan memberikan informasi, menghibur, membujuk, dan mendorong penonton berpikir kritis. Penggunaan figure manusia dan bukan manusia direkomendasikan hanya untuk iklan produk yang terkait dan relevan. Pengunaan figure manusia sebaiknya mempertimbangan aspek sosial, budaya, dan keyakinan dari calon penonton iklan. Penggunaan warna mencolok dan kompleks dapat membantu memperoleh perhatian serius dari penonton iklan. Pengaturan ukuran dan letak tiap bagian gambar di iklan merepresentasikan urutan prioritas dalam memperkenalkan produk pada penonton atau pelanggan. Sementara itu, penggunaan teks tertulis yang pendek menunjukkan hasil sangat baik untuk menjalin komunikasi yang interaktif dan komunikatif. Pada tahap analisa, peneliti menyusun dan memaparkan satu prototype metode menarik perhatian penonton pada iklan digital yang terdiri dari tahap observasi, penampilan fisik iklan, teks tertulis di iklan, dan penyampaian pesan secara implisit atau tidak langsung.Kata Kunci: Pendekatan, menarik, perhatian, digital, iklan